1999
DOI: 10.1074/jbc.274.13.8737
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Potential Effector Molecules of the Ras-related GTPase Rap2

Abstract: In search for effectors of the Ras-related GTPase Rap2, we used the yeast two-hybrid method and identified the C-terminal Ras/Rap interaction domain of the Ral exchange factors (RalGEFs) Ral GDP dissociation stimulator (RalGDS), RalGDS-like (RGL), and RalGDSlike factor (Rlf). These proteins, which also interact with activated Ras and Rap1, are effectors of Ras and mediate the activation of Ral in response to the activation of Ras. Here we show that the full-length RalGEFs interact with the GTP-bound form of Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…The potential interaction of Ral-GDS with either activated Ras or Rap1 suggests that Ral can be activated by at least two pathways. However, although Rap1/Ral-GDS interaction has been seen in the two-hybrid system and in vitro, Rap1 fails to co-immunoprecipitate with Ral-GDS in co-transfected cells, so compartmentalisation of the proteins was suggested (Nancy et al, 1999). Here we have demonstrated that Ras activates Ral through the Ral-GDS effector in Xenopus embryos.…”
Section: Ras Is An Upstream Element Of the Ralb Pathwaymentioning
confidence: 82%
“…The potential interaction of Ral-GDS with either activated Ras or Rap1 suggests that Ral can be activated by at least two pathways. However, although Rap1/Ral-GDS interaction has been seen in the two-hybrid system and in vitro, Rap1 fails to co-immunoprecipitate with Ral-GDS in co-transfected cells, so compartmentalisation of the proteins was suggested (Nancy et al, 1999). Here we have demonstrated that Ras activates Ral through the Ral-GDS effector in Xenopus embryos.…”
Section: Ras Is An Upstream Element Of the Ralb Pathwaymentioning
confidence: 82%
“…When the activating abilities of these three eectors among Ras-family proteins are compared, Ras can activate all of the eectors (Campbell et al, 1998), Rap1 activates B-Raf and Ral-GEFs (Ohtsuka et al, 1996;Kishida et al, 1997;Zwartkruis et al, 1998), and TC21 activates B-Raf and Raf-1 (Rosa rio et al, 1999). In contrast, although R-Ras has been reported to bind Raf and Ral-GEF in a GTP-dependent fashion, the binding anities to these molecules are much lower than those of Ras (Herrmann et al, 1996;Nancy et al, 1999). Corresponding with this, R-Ras causes only a marginal increase in the activity of ERK, a down- Figure 4 Eect of R-Ras Q87L on myoblast migration.…”
Section: Discussionmentioning
confidence: 96%
“…However, we cannot rule out a role for Rap1. Because activated Rap1 and Rap2 bind many of the same effector proteins (43), it is possible that activation of either Rap1 or Rap2 is sufficient to allow B cells to migrate toward SDF-1. Unfortunately, expressing dominant-negative forms of Rap1 and Rap2 would not allow us to determine the relative roles of Rap1 and Rap2 in B cell migration because dominant-negative GTPases act by sequestering upstream activators and Rap1 and Rap2 share the same upstream activators.…”
Section: Discussionmentioning
confidence: 99%